American Humour And Realism In Mark Twain’s Narrative Technique (Texas Journal of Multidisciplinary Studies, 2025)
This article explores the intertwining of American humour and literary realism in the narrative style of Mark Twain, one of the most iconic figures in American literature. Through the analysis of Twain’s most representative works—particularly The Adventures of Tom Sawyer, The Adventures of Huckleberry Finn, and various short stories—the study examines how Twain’s humour emerges not only from comic situations but also from sharp social observation, dialectal authenticity, and psychological insight. The research argues that Twain’s humour, rooted in regionalism and vernacular speech, serves as both entertainment and critique, enhancing the realism of his characters and settings while offering commentary on broader sociopolitical issues in 19th-century America.